How does public debt affect economic growth? The case of the new EU member states - Fejzula Beha; Filipos Ruxho (Global Business & Finance Review (GBFR), 2024)
Purpose: This study investigates how public debt affects economic growth in eleven new EU member states in Central and South-Eastern Europe from 2000 to 2021. These countries are categorized into the Balkan, Baltic, and Visegrad groups based on their economic characteristics. Design/methodology/approach: The analysis employs a panel Autoregressive Distributed Lag (ARDL) model to explore the relationship between public debt and GDP growth, accounting for variables such as trade openness, population growth, inflation, and foreign direct investment. Findings: The results indicate a significant negative correlation between increasing public debt levels and GDP growth, with the effect being especially pronounced in Balkan countries. This negative association is evident both in the short term and long term, highlighting a greater sensitivity to public debt in less economically developed regions. Research limitations/implications: The study is limited by its use of annual data and its focus on specific geo-graphic areas. Despite these limitations, the research provides valuable insights into the complex relationship be-tween public debt and economic growth in new EU member states. Originality/value: This research offers important perspectives on the nuanced dynamics of public debt and econom-ic growth within the context of new EU member states, enhancing the understanding of these relationships in different economic settings.
Keywords: 650; Public debt; Economic growth; EU new member states; ARDL